2017
DOI: 10.1177/0271678x17709709
|View full text |Cite
|
Sign up to set email alerts
|

Insulin differentially affects the distribution kinetics of amyloid beta 40 and 42 in plasma and brain

Abstract: Impaired brain clearance of amyloid-beta peptides (Aβ) 40 and 42 across the blood-brain barrier (BBB) is believed to be one of the pathways responsible for Alzheimer's disease (AD) pathogenesis. Hyperinsulinemia prevalent in type II diabetes was shown to damage cerebral vasculature and increase Aβ accumulation in AD brain. However, there is no clarity on how aberrations in peripheral insulin levels affect Aβ accumulation in the brain. This study describes, for the first time, an intricate relation between plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 47 publications
5
52
1
Order By: Relevance
“…Whether brain insulin resistance has consequences similar to those in type 2 diabetes, or whether it may represent a separate type of pathology referred to as type 3 diabetes, remains to be a matter of debate. Recently, effects of hyperinsulinemia were reported concerning the clearance of Aβ peptides over the blood‐brain barrier, however, with divergent results in Aβ 1‐40 and Aβ 1‐42 , details that will need further clarification with regard to their pathological consequences. Type 2 diabetes is known to represent a risk for cognitive impairment and dementia .…”
Section: Melatonin and Inflammation In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Whether brain insulin resistance has consequences similar to those in type 2 diabetes, or whether it may represent a separate type of pathology referred to as type 3 diabetes, remains to be a matter of debate. Recently, effects of hyperinsulinemia were reported concerning the clearance of Aβ peptides over the blood‐brain barrier, however, with divergent results in Aβ 1‐40 and Aβ 1‐42 , details that will need further clarification with regard to their pathological consequences. Type 2 diabetes is known to represent a risk for cognitive impairment and dementia .…”
Section: Melatonin and Inflammation In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Additionally, exercise, especially resistance training, may affect the burden of amyloid plaques, which are associated with cognitive decline [16][17][18][19]. One study found that resistance training can directly decrease circulating insulin [20], of which an increase may affect the distribution of amyloid 40 and 42 in brain regions, resulting in the accumulation of amyloid plaques [21,22]. Holten et al note that resistance training increases glucose transporter type 4, insulin receptor, PKB-α/β and glycogen synthase protein content, which indirectly reduces the content of insulin by increasing glucose metabolism and insulin sensitivity and reducing insulin resistance [23].…”
Section: Introductionmentioning
confidence: 99%
“…On treatment with insulin, there was reversal of this complication which depicts the role of insulin deficiency behind the development of tau pathology in diabetes (Van der Harg et al, ). Insulin modulated Aβ40 and Aβ42 distribution in mice which reflects dysregulation of insulin in case of metabolic disorder as a possible reason behind altered Aβ level (Swaminathan et al, ).…”
Section: Factors Involved In Regulationmentioning
confidence: 99%
“…Insulin deficiency or insulin resistance is the major etiology behind the development of diabetes. Apart from its role in maintenance of blood glucose, it is also suggested to be involved in AD-like cognitive deficits (Swaminathan et al, 2018).…”
Section: Insulinmentioning
confidence: 99%